2021
DOI: 10.3390/molecules26113092
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Genetically Very Close Accessions of Sweet Orange (Citrus sinensis L. Osbeck) by Laser-Induced Breakdown Spectroscopy (LIBS)

Abstract: The correct recognition of sweet orange (Citrus sinensis L. Osbeck) variety accessions at the nursery stage of growth is a challenge for the productive sector as they do not show any difference in phenotype traits. Furthermore, there is no DNA marker able to distinguish orange accessions within a variety due to their narrow genetic trace. As different combinations of canopy and rootstock affect the uptake of elements from soil, each accession features a typical elemental concentration in the leaves. Thus, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Olive oil, another extensively studied agricultural product, demonstrates a strong link between quality and geographical factors. The Stelios Couist team pioneered the application of machine learning-assisted LIBS technology for olive oil classification, yielding highly accurate classification outcomes. , Furthermore, in citrus breeding, Magalhaes et al effectively employed LIBS technology to distinguish different citrus varieties, introducing a novel research avenue for citrus breeding.…”
Section: Application Of Libs Technology In Agricultural Product Analysismentioning
confidence: 99%
“…Olive oil, another extensively studied agricultural product, demonstrates a strong link between quality and geographical factors. The Stelios Couist team pioneered the application of machine learning-assisted LIBS technology for olive oil classification, yielding highly accurate classification outcomes. , Furthermore, in citrus breeding, Magalhaes et al effectively employed LIBS technology to distinguish different citrus varieties, introducing a novel research avenue for citrus breeding.…”
Section: Application Of Libs Technology In Agricultural Product Analysismentioning
confidence: 99%
“…Instrumental parameters of LIBS influence the interaction of the laser pulse with the sample and the acquisition of the analytical signal. Thus, a 2 3 factorial design with a central point (Table 2) was used to optimize the variables at three levels: (i) laser pulse energy (29.73, 42.29, and 54.86 mJ), (ii) delay time (0.5, 1.0, and 1.5 µs), and (iii) the analytical signal acquisition time (1,11, and 20 µs) to obtain the LIBS spectrum. A total of 11 experiments were carried out.…”
Section: Optimization Of Instrumental Parameters For Libs Analysesmentioning
confidence: 99%
“…Photonic techniques and machine learning algorithms have been extensively used to improve agricultural management in the past few years, mainly due to their high accuracy associated with their fast response, low analytical cost, simplified sample preparation, and environmentally clean techniques [ 7 , 8 , 9 , 10 , 11 , 12 ]. Recently, our research group demonstrated the potential application of the Fourier-transform infrared (FTIR) and Laser-induced breakdown spectroscopy (LIBS) for seed vigor classification [ 5 , 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Larios et al [ 42 ] discriminated low and high-vigor soybean seed lots, using LIBS along with machine learning techniques such as Principal Components Analysis (PCA), Support Vector Machines (SVMs), Linear Discriminant Analysis (LDA), Quadratic Discriminant Analysis (QDA), and k-Nearest Neighbors (k-NN). Furthermore, LIBS has been used for discrimination of both the cultivar [ 43 , 44 ] and geographical origin [ 45 ] of different kinds of foodstuffs. In that view, Perez-Rodriguez et al [ 43 ], after selecting the emission lines of carbon (C), calcium (Ca), iron (Fe), magnesium (Mg), and sodium (Na) and using the Extreme Gradient Boosting (XGBoost) algorithm, developed a k-NN model able to predict the cultivar of brown rice with accuracy up to 86%.…”
Section: Libs Applications In Food Analysismentioning
confidence: 99%
“…In that view, Perez-Rodriguez et al [ 43 ], after selecting the emission lines of carbon (C), calcium (Ca), iron (Fe), magnesium (Mg), and sodium (Na) and using the Extreme Gradient Boosting (XGBoost) algorithm, developed a k-NN model able to predict the cultivar of brown rice with accuracy up to 86%. Similarly, Megalhães et al [ 44 ] used LIBS combined with some machine learning algorithms (i.e., PCA, PLSR, etc.) and achieved the successful discrimination of some sweet oranges, with similar DNA, with high accuracy.…”
Section: Libs Applications In Food Analysismentioning
confidence: 99%